Handel Design for Wok Frypan Type Pan - Budi Utomo, Muhammad Fitri (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
ABSTRACT Yogyakarta metal SMEs are required to continue to innovate and develop technology to be able to adapt to market demands. Metal IKM is under the auspices of the Yogyakarta Metal Technical Implementation Unit (UPT). Metal UPT is responsible for carrying out research and studies on metal quality as well as studies on the development of metal product design technology. A large number of products from abroad makes metal SMEs must be able to compete in the market. Metal SMEs must be able to provide superiority to their products, one of the advantages that is built is presenting cookware designs, especially frypan works so that they have a competitive advantage. This study aims to determine the attributes and technical responses of the Wok Frypan-type handle product and to create a product prototype. Product technical attributes and responses were searched using the QFD method based on consumer desires. To overcome the problem of contradictions in QFD, the TRIZ method is used. The research resulted in a prototype design based on 11 attributes and 12 technical responses to the wok frypan-type Handel product. Keywords: Handle, QFD, TRIZ, Wok frypan.